"Carbon Bombs" - Mapping key fossil fuel projects. (July 2022) - Kühne, Kjell; Bartsch, Nils; Tate, Ryan Driskell; Higson, Julia; Habet, André
Abstract: Meeting the Paris targets requires reducing both fossil fuel demand and supply, and closing the "production gap" between climate targets and energy policy. But there is no supply-side mitigation roadmap yet. We need criteria to decide where to focus efforts. Here, we identify the 425 biggest fossil fuel extraction projects globally (defined as >1 gigaton potential CO2 emissions). We list these "carbon bombs" by name, show in which countries they are located and calculate their potential emissions which combined exceed the global 1.5 °C carbon budget by a factor of two. Already producing carbon bombs account for a significant percentage of global fossil fuel extraction. But 40% of carbon bombs have not yet started extraction. Climate change mitigation efforts cannot ignore carbon bombs. Defusing them could become an important dimension of climate change mitigation policy and activism towards meeting the Paris targets. So far, few actors, mainly from civil society, are working on defusing carbon bombs, but they are focussing on a very limited number of them. We outline a priority agenda where the key strategies are avoiding the activation of new carbon bombs and putting existing ones into "harvest mode". Highlights: There are 425 fossil fuel projects with >1 Gt CO2 potential emissions globally. Carbon bombs' potential emissions exceed a 1.5 °C carbon budget by a factor of two. 40% (169 out of 425) of carbon bombs had not started extraction in 2020. Defusing carbon bombs should be a priority for climate change mitigation policy.